2005
DOI: 10.1016/j.jasms.2005.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel mass spectrometric method to distinguish isobaric monosaccharides that are phosphorylated or sulfated using ion-pairing reagents

Abstract: Phosphorylation and sulfation are two important biological modifications present in carbohydrates, proteins, and glycoproteins. Typically, sulfation and phosphorylation cause different biological responses, so differentiating these two functional groups is important for understanding structure/function relationships in proteins, carbohydrates, and metabolites. Since phosphorylated and sulfated compounds are isobaric, their discrimination is not possible in routinely utilized mass spectrometers. Thus, a novel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Although they have yet to be used in IMS studies, Desaire and coworkers have shown that ion-pairing reagents can be used to bind and ionize certain functionalized (e.g., phosphorylated or sulfated) saccharide species [21,22]. Due to the acidity of these functional groups, such ion-pairing reagents are typically oligomers of basic amino acid residues, such as trilysine [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they have yet to be used in IMS studies, Desaire and coworkers have shown that ion-pairing reagents can be used to bind and ionize certain functionalized (e.g., phosphorylated or sulfated) saccharide species [21,22]. Due to the acidity of these functional groups, such ion-pairing reagents are typically oligomers of basic amino acid residues, such as trilysine [22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the acidity of these functional groups, such ion-pairing reagents are typically oligomers of basic amino acid residues, such as trilysine [22]. These reagents make it possible to differentiate between phosphorylated and sulfated species based on characteristic fragment ions produced upon collision-induced dissociation [21]. Peptide-based reagents are also appealing because, unlike metal cations, they have inherent structure that may be flexible.…”
Section: Introductionmentioning
confidence: 99%
“…Other MS methods, such as matrix-assisted laser desorption/ionization (MALDI) [21] and electrospray ionization (ESI) [22], have been recently reported to distinguish phosphorylation and sulfation. In MALDI analysis, sulfated and phosphorylated products ionize somewhat differently, and these differences could potentially be used to distinguish phosphate and sulfate in an unknown compound [21].…”
mentioning
confidence: 99%
“…In MALDI analysis, sulfated and phosphorylated products ionize somewhat differently, and these differences could potentially be used to distinguish phosphate and sulfate in an unknown compound [21]. In ESI analysis, ion-pairing reagents have been utilized to complex with singly phosphorylated or sulfated monosaccharides [22]. The isobaric ion-pairing complexes can be differentiated in MS/MS experiments because of their different chemical reactivities.…”
mentioning
confidence: 99%
See 1 more Smart Citation